"Air I Breathe": Songwriting as Literacy Practices of Remembrance. (June 2020) - Deroo, Matthew R.; Watson, Vaughn W. M.
This qualitative study, based on data from an ongoing after-school literacy and songwriting initiative, examines the multiliteracy practices of Noriah Rose and Koral, Black adolescent girls, and their socially situated meaning-making and sharing about loss. Specifically, we asked, "In what ways do youth grapple with complicated meanings of loss as they share creative and artistic songwriting practices?" We build upon interdisciplinary framings in literacy and social science research to advance new theoretical understandings of literary practices of remembrance, highlighting the public sharing of independently authored digital compositions across various audiences through song. We conceptualize youths, enacting literacy practices of remembrance, as demonstrating three socially situated stances of sharing: evoking a passed-on narrative complicating temporality and permanence, historicizing artistic cultural expression, and demonstrating mutual sharing and stewardship of loss. We argue that various communities supported youths' meaning-making about loss, and we offer implications for teaching, research, and practice.